2020
DOI: 10.1186/s12886-020-01363-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pediatric eye injuries requiring hospitalization in rural areas of Wenzhou and Changsha, China: a 10-year retrospective study

Abstract: Background: The aim of this study was to review the demographic and characteristic distribution data of serious rural pediatric eye injuries in Wenzhou and Changsha, located in Zhejiang Province in East China and Hunan Province in Central China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
7
16
2
Order By: Relevance
“…Similar to other studies worldwide, our study showed that boys were more susceptible to suffer from open globe injuries than girls [ 2 - 11 ]. The male predisposition could be explained by the boy’s tendency to involve in more dangerous activities that make them prone to the risk of experiencing a traumatic eye injury.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to other studies worldwide, our study showed that boys were more susceptible to suffer from open globe injuries than girls [ 2 - 11 ]. The male predisposition could be explained by the boy’s tendency to involve in more dangerous activities that make them prone to the risk of experiencing a traumatic eye injury.…”
Section: Discussionsupporting
confidence: 91%
“…Other objects such as glasses, darts, stationary, firework, stone, wire, and even animals have been reported to cause open globe injuries [5][6][7]11]. This study found two cases (4.3%) where the injuries had been caused by an animal attack, which was also previously reported by Li et al (1.4%) [11].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The pattern of injuries in children appears somewhat different: of 1125 children with globe injuries 73.8 % were male and, of the mechanical injuries, penetrating injuries were the most frequent (68.4 %) and globe ruptures uncommon at 8.2 % [7].…”
Section: Characteristics Of Injuries Caused By Fallsmentioning
confidence: 99%